2015
DOI: 10.3389/fimmu.2015.00427
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Immunological Mechanisms Following Mucosal Vaccination of Finfish

Abstract: Mucosal organs are principle portals of entry for microbial invasion and as such developing protective vaccines against these pathogens can serve as a first line of defense against infections. In general, all mucosal organs in finfish are covered by a layer of mucus whose main function is not only to prevent pathogen attachment by being continuously secreted and sloughing-off but it serves as a vehicle for antimicrobial compounds, complement, and immunoglobulins that degrade, opsonize, and neutralize invading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 132 publications
(138 reference statements)
3
44
0
Order By: Relevance
“…They observed that molecular markers linked to nutrient digestion and absorption were high in the anterior (AI) and middle intestine (MI) while the posterior intestine (PI) predominantly expressed genes linked to immune defence mechanisms. These observations are in line with other scientists who showed that the AI and MI are mainly responsible for nutrient digestion and absorption [104,105] while the PI is responsible for induction of innate immune responses linked to activation of adaptive immunity in teleosts ish [106][107][108][109].…”
Section: Nutrigenomics In Aquaculturesupporting
confidence: 92%
“…They observed that molecular markers linked to nutrient digestion and absorption were high in the anterior (AI) and middle intestine (MI) while the posterior intestine (PI) predominantly expressed genes linked to immune defence mechanisms. These observations are in line with other scientists who showed that the AI and MI are mainly responsible for nutrient digestion and absorption [104,105] while the PI is responsible for induction of innate immune responses linked to activation of adaptive immunity in teleosts ish [106][107][108][109].…”
Section: Nutrigenomics In Aquaculturesupporting
confidence: 92%
“…Table 1, Table 2 and Table 4 show that intraperitoneal injectable vaccines account for the largest proportion of vaccines developed against S. agalactiae in tilapia and the general observation is that injectable vaccines produce higher protection than mucosal vaccines [37,38]. The advantage of using injectable vaccines is that it is easy to optimize the antigen dose that corresponds with protection, thereby making it is easy to correlate the antigen dose with vaccine protection [39].…”
Section: Vaccine Delivery Systemmentioning
confidence: 99%
“…Despite that, immersion bath stimulates immune response, mainly in mucosal tissues such as skin [37]. The intraperitoneal injection of TT-P0 plus immersion bath with inclusion bodies received by group 3 was ineffective in terms of vaccine efficacy, although some immune parameters were improved.…”
Section: Discussionmentioning
confidence: 99%